The neural basis of visuospatial perception in Alzheimer's disease and healthy elderly comparison subjects: An fMRI study - Thiyagesh, Subha N.; Farrow, Tom F.D.; Parks, Randolph W.; Accosta-Mesa, Hector; Young, Claire; Wilkinson, Iain D.; Hunter, Michael D.; Woodruff, Peter W.R. (Psychiatry research. Neuroimaging, 2009)
The neural basis of visuospatial deficits in Alzheimer's disease is unclear. We wished to investigate the neural basis of visuospatial perception in patients with Alzheimer's disease compared with healthy elderly comparison subjects using functional magnetic resonance imaging (fMRI). Twelve patients with AD and thirteen elderly comparison subjects were investigated. The patients were recruited from the local clinic and comparison subjects were from spouses and community. All participants underwent fMRI whilst viewing visuospatial stimuli and structural MRI, and findings were analysed using voxel-based morphometry. The comparison group activated V5, superior parietal lobe, parieto-occipital cortex and premotor cortices. The AD group demonstrated hypoactivation in the above regions and instead showed greater activation in inferior parietal lobule and activated additional areas. There was no structural atrophy above and beyond that found globally in patients in the identified regions of BOLD activation. To our knowledge, this is the first study to explore the neuroanatomy of perception of depth and motion in Alzheimer's disease. These specific functional deficits in AD provide evidence for an underlying patho-physiological basis for the clinically important symptom of visuospatial disorientation in patients with AD.